Ronald Reagan, the movie and other episodes in political demonology - Rogin, Michael Paul (University of California Press, 1988)
"Fresh, provocative, and full of vitality, this is a first-rate contribution to the study of political culture. It should be read not only by political scientists, political theorists, and sociologists, but also by students of American studies and literature."--Sheldon Wolin, Princeton University